What determines online consumers to migrate from PCs to mobile devices? - An empirical approach on consumers' internet cross-channel behaviours. (2016) - Tang, Dingna; Yang, Yimin; Yan, Ying; Zhou, Ming
With the improvement of telecommunication and wireless internet-access technologies, smart mobile devices have been extensively applied for mobile shopping. In this paper, PPM model is taken as a theoretical framework and an empirical research method is employed to determine the antecedents influencing consumers' decisions on migrating from PC-based shopping to mobile shopping. We found that inconvenience, perceived high price, security, perceived usefulness, and perceived ease of use are the significant antecedents influencing consumers' channel migration intention of choosing mobile shopping; while the hypothesis of switching cost is not supported.